Determinants of Total Quality Management and Institutional Pressure towards Project Performance: A Review of Literature - Al Alyani, Wafa Rashid; Lee, Chia Kuang (Human Resource Management Academic Research Society (HRMARS), 2024)
The purpose of this paper is to systematically review the literature published on various aspects of project performance. This paper highlights the importance of total quality management (TQM) with respect to project success. The study is based on secondary information collected through the review of existing literature. It was found that TQM factors are important factor in the organization's performance and improved efficiency. It is crucial since concentrating on the execution and success of the project helps the organisation, employers, and project managers. Project managers can make better decisions, recognise their rights and obligations, and comprehend and manage risk when TQM is combined with suitable governance. This study provides theoretical framework that includes TQM factors, institutional elements, project governance and project performance. Based on the comprehensive review of literature it is suggested that future research should aim on confirming the developed framework for project performance and success.